P046 Ensuring quality-assured and personalized online self-testing within a market-driven context. (14th July 2019) - Vermey, Koenraad; Daas, Chantal Den; Zweers, Wessel; Bergen, Jan Van; Bos, Hanna
Abstract : Background: The number of private and online providers of STI tests is increasing in the Netherlands. The autonomy and accessibility of online self-testing may contribute to timely diagnosis, lower healthcare costs and shorter waiting lists at STI clinics. But ill-informed self-testing can also lead to underdiagnosis and insufficient partnermanagement of STIs. To improve linkage to high quality private testing providers the online advice application Advies.chat was launched in 2017. We assessed process indicators for the successful implementation of this online advice instrument in 2018. Methods: The application generates tailored advices based on clinical guidelines. The questionnaire takes into account personal characteristics, sexual behaviour, sexual risks and symptoms. The advice refers to STI testing providers if testing is indicated and explains which specific STIs need to be tested for. All test advices refer to GP's and the specific diagnostic tests offered by selected online testing providers. Key populations (MSM, sex workers and young people < 25 years) are also referred to STI clinics. Anonymous process data from the Advies.chat database were analysed. Results: Advies. chat was visited 337, 736 times in 2018; 113, 257 visitors started the questionnaire, 17, 449 the chatbot. Visits increased on Sundays, peaked on Mondays and decreased during the week. The most indicated reason for using Advies.chat was the 'possibility of being STI or HIV infected' (75%). Around 60% finished the questionnaire, leading to 65, 736 advices and 8, 700 clicks to online self-test providers. Conclusion: Online self-management tools can play a keyrole in improving the quality of the growing online STI testing market. Advies.chat shows that online triage and tailored advice is feasible and increases traffic to quality testing providers. The contribution of Advies.chat to the estimated 430, 000 consultations at GP's and STI clinics in the Netherlands is sizable. Methods need to be developed to assess the impact of online self-management and self-testing on STI control. Disclosure: No significant relationships.